Faktor - Faktor Yang Mempengaruhi Proses Pengkodean Diagnosis Di Rumah Sakit Umum Daerah Cilacap - Febriana, Dina; Hakim, Agya Osadawedya; Indira, Zahrasita Nur; Anggraeni, Okti (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2024)
Hospitals are health institutions that provide medical services to individuals as a whole, including inpatient, outpatient, and emergency care. Hospitals need to improve the quality of their services. This can be done by having a good medical record unit. Medical records are documents that contain information about the patient's identity, examination, treatment, procedures, and other services provided to the patient. An important data processing to store data in medical records is coding. Classifying and providing codes for disease diagnosis is known as coding. Writing codes on medical records must be precise and accurate. The impact of coding errors can affect the quality of medical records. Based on an initial survey related to coding carried out at Cilacap Regional Hospital, a problem was found that officers had difficulty reading the doctor's writing. This study aims to determine what factors influence the diagnosis coding process at Cilacap Regional Hospital. This research is a type of qualitative research with data collection method instruments through observation and interviews. The research subjects amounted to 2 people, namely coder officers and the head of the medical records unit. The results of the study obtained several factors that influence the coding process including; Writing a diagnosis that is difficult to read, incompleteness in medical records can affect the coding process that will be carried out by the coder, and the absence of a medical dictionary as a coding support book in finding unknown terms in coding.